Quasi-phase-matched high-order harmonic generation using tunable pulse trains - Kevin O'Keeffe (Optics Express, 2014)
A simple technique for generating trains of ultrafast pulses is demonstrated in which the linear separation between pulses can be varied continuously over a wide range. These pulse trains are used to achieve tunable quasi-phase-matching of high harmonic generation over a range of harmonic orders up to the harmonic cut-off, resulting in enhancements of the harmonic intensity in excess of an order of magnitude. The peak enhancement depends on the separation between pulses, as well as the number of pulses in the train, representing an easily tunable source of quasi-phase-matched high harmonic generation.